A Study of Financial Inclusion Efforts among Women and Its Impact on the Women Empowerment (International Journal of Innovative Research in Engineering & Management, 2023)
Financial inclusion has been a major  concern in the government in recent years. Financial  inclusion refers to the availability to both individuals and  businesses of useful and cost-effective financial goods and  services, including payments, transactions, savings, credit,  and insurance, that are provided in a sustainable and  responsible manner. This will help the people to grow and  develop. The impact of financial inclusion is positively on  every aspect of society. In a single study it is not possible  to understand the role of financial inclusion. Researcher  has emphasized on the women empowerment aspect in the  present study.
Keywords: Financial Inclusion; Women Empowerment; Social Growth; Financial Security